Geoinformation Analysis of Regional Climatic Changes in the Central and Western Russian Arctic for Railway Development - Kostianoy Andrey Gennad'evich; Gvishiani Alexei; Rozenberg Igor' Naumovich; Krasnoperov Roman; Gvozdik Sofia A.; Lebedev Sergey; Nikitina Isabella; Dubchak Irina; Shevaldysheva Olga; Sergeev Vladimir; Gvozdik Georgy (Russian Journal of Earth Sciences)
The Arctic Zone of the Russian Federation is characterized by the rapid growth of the mining industry, aimed at the extraction of oil, gas, coal, and ores, including rare earth metals. Railways are essential in the transportation of these resources to different regions of Russia for processing and export. Part of the cargo delivery is performed via the Arctic ports connected to the railway network. Rapid climate change, including regional climate warming, is among the compromising factors for the operation of the Arctic transport infrastructure. System analysis of climatic processes and assessment of potential hazards that they may induce requires adequate geoinformation support. This paper presents the results of spatio-temporal variability analysis of various hydrometeorological parameters for selected railway mainlines within the Arctic region. For this purpose, a new geoinformation method based on the Hovmöller diagrams was elaborated. This tool is useful for representing climate dynamics along the specified railway mainlines over several decades. It allows us to determine railway sections affected by anomalous climatic conditions on the variable time scale. The presented Hovmöller diagrams proved to be an efficient instrument for the regional climate change representation. It might be quite useful for railway infrastructure maintenance, planning, operation, and adaptation.